MARKETING STRATEGIES FOR SMALL BUSINESSES & START-UPS WHILE GOING INTERNATIONAL - Sapayev Axmed Durdibayevich (Modern American Journals, 2025)
A marketing strategy is a comprehensive plan designed to accomplish the long-term goals of an enterprise, which includes a study of market needs, analysis of consumer behavior, product positioning, and the formation of a competitive advantage. The strategy outlines how the company navigates the market, which market segments it focuses on, and what value it offers.
Keywords: Positioning; formation; strategy